TRANSFORMATION OF GIRL'S IDENTITY IN THE NOVEL: A LITERARY PSYCHOLOGICAL APPROACH - Septiaji, Aji; Nahdi, Dede Salim; Syarifah, Eva Fitriani; Majid, Sheikha (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2025)
This research examines the process of girls' identity transformation through the character of Alice in Lewis Carroll's Alice's Adventures in Wonderland using a literary psychology approach. Alice is described as a girl who experiences various internal and external conflicts during her adventures in the fantasy world of Wonderland. This research uses qualitative content analysis method. The literary psychology approach uses Erik Erikson's psychosocial theory, especially in the stages of industry vs. inferiority and identity vs. role confusion. The changes that Alice experiences emotionally, cognitively and socially are analyzed as a representation of the psychological journey of girls in forming self-identity in the midst of uncertain world. The world of Wonderland is interpreted as a symbol of the subconscious that presents various challenges to Alice's self-stability. The results show that Alice's adventures reflect the self-discovery of a growing girl, learning to know herself and building courage and independence in the midst of the absurdity of reality. This research shows that children's literature can be a reflective medium for the complexity of children's psychological development, especially in the formation of self-identity.